España y la UE: objetivo ideológico y proyecto político (1978-2018) - Bar Cendón, Antonio (Revista de Derecho Político, 2018)
Resumen: El reingreso en el contexto europeo, del que España fue expulsada tras el final de la Segunda Guerra Mundial, ha sido durante largo tiempo el objeto del componente ideológico y del proyecto político de la práctica totalidad de las fuerzas políticas españolas. El ingreso de España en las Comunidades Europeas, en enero de 1986, vino a suponer la realización de ese objetivo ideológico y de ese proyecto político. Desde entonces, España experimentó importantes cambios que mejoraron notablemente su estructura económica, pero también otros aspectos políticos y sociales. Estos cambios han sido descritos y analizados por la doctrina científica con todo detalle y extensión. Este trabajo, sin embargo, trata de describir y analizar cuáles han sido las aportaciones de España al proceso de integración europeo y su desarrollo en cada fase del mismo, y lo hace partiendo precisamente de lo que fueron los planteamientos políticos e ideológicos de las principales fuerzas políticas del momento. Algo que no se ha hecho hasta el presente con la debida extensión e interés que merece el tema. Abstract: The return to the European context, from which Spain was expelled after the end of the Second World War, has been the object of the ideological component and of the political project of almost all of the Spanish political forces for a long time. The admission of Spain into the European Communities, in January 1986, meant the realization of that ideological objective and political project. Since then, Spain experienced important changes that significantly improved its economic structure, but also other political and social aspects. All of these changes have been extensively described and analyzed by the specialized literature. This paper, however, tries to describe and analyze Spain’s contributions to the European integration process at each phase of its development, and it does so departing precisely from a description of the political and ideological positions of the political forces of that period. This is something that has not been done so far, with the extension and interest that the subject deserves. Summary: 1. Introduction. 2. Europe as an ideological objective. 3. Europe as a political project. A) The first step: The Single European Act. B) Citizenship and cohesion: The Treaty of Maastricht. C) The foreign role and the social policy: The Treaty of Amsterdam. D) Enhancing the institutional position: The Treaty of Nice. E) From toughness to concession: The European Constitution. F) Weakness and relocation: The Treaty of Lisbon. 4. Conclusion.